Reconstruction of Governance and Epistemic Transformation of Islamic Education Through the Integration of Madrasah-Based Management and Curriculum Innovation - Mochammad Bukhori Hasyim; Mufidah Cholil; Khotimatus Sholikhah (Al-Qalam Institue, 2026)
This study aims to analyze the reconstruction of Islamic educational governance through the integration of Madrasah-Based Management and curriculum innovation as a strategy for the epistemic transformation of contemporary Islamic education in Indonesia. The study employed a qualitative approach using a systematic literature review of national and international publications published between 2021 and 2026. Data were collected from scientific articles indexed in SINTA, Scopus, and DOAJ, as well as official reports from the Indonesian Ministry of Religious Affairs and relevant academic books. The findings indicate that the integration of Madrasah-Based Management and curriculum innovation strengthens institutional autonomy, enhances governance effectiveness, supports data-driven and participatory management, and promotes a more adaptive, integrative, and student-centered learning paradigm. The study also found that the transformation of Islamic education requires digitalized governance systems, transformational leadership, and the holistic integration of religious and modern sciences to improve educational quality and institutional competitiveness. The implication of this study is the development of an integrative model of transformative Islamic education that can serve as a strategic framework for strengthening governance reform, curriculum innovation, and epistemological reconstruction in responding to contemporary educational challenges.